Impact of endoscopy system, high definition, and virtual chromoendoscopy in daily routine colonoscopy: a randomized trial - Roelandt, Philip; Demedts, Ingrid; Willekens, Hilde; Bessissow, Talat; Braeye, Lieve; Coremans, Georges; Cuyle, Pieter-Jan; Ferrante, Marc; Gevers, Anne-Marie; Hiele, Martin; Osselaer, Maggy; Tack, Jan; Tejpar, Sabine; Ulenaers, Marijke; Van Assche, Gert; Van Cutsem, Eric; Van Gool, Stijn; Vannoote, Jaarke; Vermeire, Severine; Bisschops, Raf (Endoscopy, 2019)
Background To improve detection of mucosal lesions during colonoscopy a number of imaging modalities have been suggested, including high definition and virtual chromoendoscopy. Given the theoretical advantage of these new imaging techniques, we aimed to investigate their use for the detection of polyps in patients referred for colonoscopy in a large tertiary hospital.Methods Demographic, endoscopic, and histological data from 1855 consecutive patients undergoing colonoscopy were collected prospectively. Patients were randomly assigned to three endoscopy systems (Fujinon, Olympus, or Pentax) in combination with four modalities: conventional white-light colonoscopy (n = 505), high definition white-light colonoscopy (n = 582), virtual chromoendoscopy (n = 285) and high definition virtual chromoendoscopy (n = 483).Results The mean adenoma detection rate (ADR) was 34.9 %, and the adenoma per colonoscopy rate (APCR) was 2.1. No significant differences were noted between the three endoscopy systems. Moreover, no differences in ADR or APCR were observed between the four imaging modalities. High definition white-light colonoscopy resulted in a significantly higher detection of sessile serrated adenomas (8.2 % vs. 3.8 %; P < 0.01) and adenocarcinomas (2.6 % vs. 0.5 %; P < 0.05) compared with the conventional procedure.Conclusions No significant differences in ADR or APCR between different endoscopy systems, high definition, and/or virtual chromoendoscopy could be observed in routine colonoscopies in the general population. High definition endoscopy was associated with a significantly higher detection rate of serrated adenomas and adenocarcinomas.